Sensory Integration of a Mobile Robot Using the Embedded System Odroid-XU4 and ROS - Gamarra, Daniel; Legg, Andrei; Cuadros, Marco; Silva, Emanueli (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
This article describes the development of a sensory integration architecture of a robotic vehicle using the Odroid-XU4 device and the Robot Operating System (ROS). The ODROID and ROS help us to integrate the hardware components of the robot, develop new tools, as the web interface and Arduino integration, and use different ROS packages for the construction, functioning and navigation of the robot. Also, a 3D model of the robot for simulation was designed and the integration of different sensors allowing to execute basic mobile robot navigation behaviors, such as, obstacle avoidance, remote control and SLAM.